2021
DOI: 10.2169/internalmedicine.6094-20
|View full text |Cite
|
Sign up to set email alerts
|

Adult Krabbe Disease That Was Successfully Treated with Intravenous Immunoglobulin

Abstract: Krabbe disease involves the accumulation of neurotoxic metabolites due to lysosomal galactocerebrosidase enzyme deficiency, which results in widespread demyelination of central and peripheral nerves. Generally, Krabbe disease presents as spastic paraplegia with a slow progressive course; however, some cases may show clinical symptoms similar to those of chronic inflammatory demyelinating polyneuropathy (CIDP). No previously reported studies have investigated the efficacy of intravenous immunoglobulin (IVIg) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…It was suggested that in certain KB cases, IVIg may be considered as a form of therapy. 66 Pentraxin-3 (PTX3), a soluble pattern recognition receptor and a regulator of innate immunity, 67 was seen in the CNS of GALC-deficient Krabbe patients and twitcher mice. PTX3 may exert a protective role by reducing the neuroinflammatory response that occurs in the spinal cord of GALC-deficient animals.…”
Section: Therapeutic Approaches For Treatment Of Krabbe Diseasementioning
confidence: 99%
“…It was suggested that in certain KB cases, IVIg may be considered as a form of therapy. 66 Pentraxin-3 (PTX3), a soluble pattern recognition receptor and a regulator of innate immunity, 67 was seen in the CNS of GALC-deficient Krabbe patients and twitcher mice. PTX3 may exert a protective role by reducing the neuroinflammatory response that occurs in the spinal cord of GALC-deficient animals.…”
Section: Therapeutic Approaches For Treatment Of Krabbe Diseasementioning
confidence: 99%
“…According to some case reports, HSCT may be effective in treating adult-onset GLD patients ( Sharp et al, 2013 ). Moreover, the intravenous injection of gamma globulin has been effective in treating adult-onset GLD patients ( Fukazawa et al, 2021 ). Symptomatic and supportive therapies are still the main clinical regimens for treating adult-onset GLD patients.…”
Section: Therapiesmentioning
confidence: 99%